2001
DOI: 10.1590/1809-43922001312298
|View full text |Cite
|
Sign up to set email alerts
|

Resistência á submersão de ácaros (Acari: Ribatida) terrestres de florestas inundáveis e de terra firme na Amazônia central em condições experimentais de laboratório

Abstract: RESUMO -Espécimens de Rostrozetes foveolatus foram obtidos de duas florestas inundáveis (várzea e igapó) e de duas florestas secundárias (terra firme) da Amazônia Central. As populações foram comparadas para a obtenção da taxa de sobrevivência em experimentos de laboratório nas condições submersas e não submersas. As coletas no igapó foram efetuadas em três períodos de 1992: antes (fevereiro: serapilheira não submersa), no início (abril: serapilheira submersa) e no pico da inundação (julho: serapilheira submer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…Obviously, being parthenogenetic, species of the genus Rostrozetes may invade very different types of habitat, be it rainforest, secondary forest, or open terrain, e.g., cultivated areas, where this genus may become a dominant element of the fauna (Woas, 2002). Moreover, Rostrozetes species occur in periodically flooded areas and are apparently capable of living under water for time intervals longer than 290 days (Franklin et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, being parthenogenetic, species of the genus Rostrozetes may invade very different types of habitat, be it rainforest, secondary forest, or open terrain, e.g., cultivated areas, where this genus may become a dominant element of the fauna (Woas, 2002). Moreover, Rostrozetes species occur in periodically flooded areas and are apparently capable of living under water for time intervals longer than 290 days (Franklin et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…The succession of these species of mites in decomposing leaf litter was already demonstrated in the soil of European forests (Wallwork, 1983;Wunderle et al, 1989). In Central Amazon, their high dominance in relation to the total invertebrate community, and great specie diversity was already confirmed (Franklin et al, 2001a). But their participation in the decomposing process is still unclear (Ribeiro & Schubart, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Submerged adults of the terrestrial oribatid mite, Rostrozetes foveolatus (Haplozetidae), showed a flood resistance up to 684 days in the laboratory. The average survival time was significantly higher in animals collected from white‐ and blackwater floodplains (≥111 days) compared with those from uplands (≥47 days) (Franklin et al ., 2001). Activity depended mainly on the availability of sufficient, dissolved oxygen in the water and on the presence of well‐developed plastron‐retaining cuticular structures (cf.…”
Section: Adaptationsmentioning
confidence: 99%
“…Na Amazônia, os estudos sobre ácaros Gamasina são escassos, principalmente relacionados a famílias especifícas como Laelapidae. Estudos sobre a acarofauna edáfica são relatados a partir de Beck (1967), demonstrando que metade da ácarofauna da Amazônia Central é composta por ácaros oribatídeos e não Gamasina (Franklin et al, 2001;2006;2007;Santos et al, 2008). A abundância de ácaros edáficos, incluindo os Laelapidade já é relatada nos biomas Cerrado, Caatinga e Mata Atlântica (Mineiro & Moraes, 2001;Silva et al, 2004;Castilho & Moraes, 2010;Azevedo, 2017).…”
Section: Laelapidaeunclassified